FRI0435 Salivary Epidermal Growth Factor (EGF) in SjÖGren's Syndrome: Association between Salivary EGF Levels and the Severity of Intraoral Manifestations. (10th June 2014) - Azuma, N.; Katada, Y.; Kitano, S.; Sekiguchi, M.; Kitano, M.; Nishioka, A.; Hashimoto, N.; Matsui, K.; Iwasaki, T.; Sano, H.
Abstract : Background: Xerostomia accompanied in patients with Sjögren's syndrome (SS) relates to reduced salivary flow rate as a result of salivary gland dysfunction. Dry mouth causes various intraoral manifestations such as refractory stomatitis, ulcer and atrophic changes in the oral mucosa and tongue, and patients' quality of life (QOL) is impaired severely. These intraoral manifestations are believed to be caused mainly by a decreased clearance in the oral cavity due to hyposalivation. Because saliva has several beneficial physiological effects on the oral environment, however, qualitative changes in sialochemistry should be considered. Salivary epidermal growth factor (EGF) is considered to be an important cytoprotective factor against injuries and it contributes to wound healing and maintenance of mucosal integrity in the oral cavity. Objectives: In the present study, we examined changes in salivary EGF levels and assessed the association between salivary EGF levels and the severity of intraoral manifestations in SS patients. Methods: Forty SS patients (27 primary SS, 13 secondary SS; 37 females, 3 males; mean age 55.4±13.2 years; mean disease duration 5.6±3.7 years) and 23 controls (18 females, 5 males; mean age 56.1±17.4 years) were enrolled. All SS patients fulfilled the 2002 American-European Consensus Group classification criteria for SS. SS patients and controls who had factors that affect the intraoral environment or saliva secretion and salivary EGF were excluded. All saliva samples were similarly collected by the chewing gum test before breakfast, with fasting. Salivary EGF levels were measured using an enzyme-linked immunosorbent assay. Subjective intraoral manifestations were evaluated using a short version of the Oral Health Impact Profile (OHIP-14), which is a self-administered questionnaire concerning oral health-related QOL (OHRQoL). Results: The OHIP-14 score in the SS group was significantly higher than that in the non-SS group (11.3±9.4 vs 7.1±7.6, p=0.037), indicating that the OHRQoL of the SS group was poor compared with that of the non-SS group. The total salivary EGF output was decreased in the SS group compared with the non-SS group (9237.6±8447.0 vs 13296.9±7907.1 pg/10 min, p =0.033), and it was markedly reduced in the SS group with long disease duration or with severe intraoral manifestations, respectively (4087.2±4356.7 pg/10 min, 6965.8±6161.1 pg/10 min). In the SS group, total salivary EGF output and salivary flow rate showed a strong positive correlation ( r s =0.824, p =0.0005), while total salivary EGF output and disease duration showed a negative correlation ( r s =–0.484, p =0.008). Further, total salivary EGF output was significantly and inversely correlated with the OHIP-14 score ( r s =–0.721, p =0.012). Conclusions: The salivary flow rate and salivary EGF levels were decreased with the progression of the disease, indicating that not only lower intraoral clearance by hyposalivation but also deterioration of saliva quality play a role in the pathogenesis of refractory intraoral manifestations in SS. Our findings provide new specific targets for therapeutic intervention for SS. References: Slade GD. Community Dent Oral Epidemiol. 1997; 25(4): 284-90. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1418